Glory beyond the Camp: Festival, Liminality, and Repentance in the Charismatic Revival - Redick, Caroline (Journal of pentecostal theology, 2020)
This article investigates whether the charismatic renewal’s Via Spiritus, with its emphasis on festival, joy, and divine empowerment, has eclipsed the Via Crucis, with its somatic pedagogy of suffering and renunciation. It explores this dynamic by contrasting two practices: the medieval Catholic pilgrimage and charismatic revival-seeking. Through exploring the overlaps between these two practices, the revival is interpreted as a liminal journey, a festival of grace, and a ritual of renunciation. At the same time, contrasting the penitential ritual of pilgrimage and revivals reveals a deficit of repentance in charismatic practice and theology.